When do consumers indulge in luxury? Emotional certainty signals when to indulge to regulate affect - Francine Espinoza Petersen (European School of Management and Technology (ESMT), 2012)
Current theorizing suggests that the valence of an affective state alone cannot explain indulgent consumption but that this is contingent on whether indulging can improve a negative state or will not hurt a positive state. This research shows that when an emotion is associated with the appraisal of uncertainty (certainty), consumers infer that their affective state can (cannot) change. As a result, people in a negative affective state will indulge more when their affect is associated with uncertainty because indulging can help repair the negative state, but people in a positive affective state will indulge more when their affective state is associated with certainty because indulging will not hurt their positive state. Reconciling earlier research reporting apparently inconsistent results linking emotional valence, affect regulation, and indulgence, these findings suggest that the certainty appraisal of specific emotions is important in predicting indulgent consumption to regulate one's affect. Implications are discussed.
urn:nbn:de:101:1-201303269144
Keywords: 650; emotion; certainty; appraisal; affect regulation; indulgence; luxury consumption